The Victim as Policy Agent? Exploring a Single Case from Denmark - Asmussen, Ida Helene (European journal on criminal policy and research, 2022)
Criminal policy processes often appear abstract and illusive, but sometimes a single criminal incident causes traceable policy impact. This article is about such an incident. A victim of a grave, violent assault published an opinion piece in a national newspaper, which sparked considerable public debate and policy actions. Some policy actions were new, and others had previously been proposed but repeatedly discarded. Based on an empirical study of the victim’s opinion piece, the ensuing media debate, and subsequent policy actions, we explore why and how certain victim’s stories capture their audience and strike a responsive chord in the public and in politicians. In the article, we analyze how the victim presents the incident as a narrative, and we identify the central features of the media debate and trace its visible impact on victim policies and legislation. We explore how some elements of the story are silenced in the political aftermath and how other elements serve as capital for politicians in pursuing their own agendas. A closer look at the policy changes in the wake of this opinion piece reveals that the story legitimizes certain political decisions and ignores victims’ desire for structural changes. Our study adds to research of “political agenda setting” by investigating the narrative power of an individual case on policy-making and by exhibiting the complex interplay between an individual story, media attention, and policy-making.